PENDIDIKAN FORMAL SEBAGAI PELESTARI TATA-NILAI DAN PEMBARU KEBUDAYAAN - Rohmad, Ali (EDUKASI: Jurnal Pendidikan Islam, 2014)
In the Islamic perspective, receptive functions that must be carried by each unit of formal education can be identified with the task of developing of habl min AllÄh (ØØ¨Ù ÙÙ Ø§ÙÙÙ ) the fabric of human relationship with God, is also the duty of man as a servant of God (Ø¹Ø¨Ø¯Ø§ÙÙÙ ) the human self servitude to Allah; being directive functions that must be carried by each educational unit can be identified with the task of developing of habl min al-Nas (ØØ¨Ù ÙÙ Ø§ÙÙØ§Ø³ ) the fabric of the relationship between humans and their universe, is also the duty of man as caliph of God on earth ( Ø®ÙÙÙØ© Ø§ÙÙÙ ÙÙØ§ÙØ£Ø±Ø¶ ) that prosperity world.